PROSES PEMBINAAN TAHAP AKHIR BAGI WARGA BINAAN DI LAPAS PEREMPUAN KELAS II B KOTA KUPANG - Samara, Finsensius; Klara Seke, Sonia; anugerah Putra Openg, Crameraldo; Anastasia Wijono, Melani; Mario P. Milo, Derryl Yosef (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
In the criminal justice system, the Correctional Institution is the last institution of the criminal justice system. Correctional facility is a place to carry out coaching for inmates and Correctional Students. Considering that the physical and psychological aspects of female inmates are different from those of male inmates, so the coaching of female inmates must be placed in a Female's Correctional Institution. This study aims to find out the process of implementing training for female inmates and obstacles for Correctional Institution in implementing coaching for female inmates and their efforts to overcome these obstacles.